Persepsi Investor Pemula di Indonesia Terhadap Reputasi Perusahaan - Rini Frima (Politeknik Negeri Padang, 2021)
This study aims to describe the perception of beginner investors on corporate reputation using the Corporate Reputation Quotient (CRQ). The CRQ used is 10 dimensions with a total indicator of 44 question items using a Likert scale. The survey was conducted using an electronic questionnaire to 49 PNP Accounting Department students who have become investors on the Indonesia Stock Exchange (IDX) in 2021. The data obtained were then processed and analyzed using descriptive statistics. The results of data processing show that the majority of beginner investors in PNP are women with an investment age of less than six months and an investment value of under Rp. 500,000. Data processing of investor perceptions of corporate reputation shows that financial performance indicators which include profitability, total assets, growth and risk are the most important factors considered by beginner investors in Indonesia. Followed by the factor of Corporate Social responsibility (CSR) in second place, which includes; ethics, and responsibility to the environment. The third position is the company's leadership, covering various factors of the company's internal resources. The two lowest factors in this survey are occupied by emotional attractiveness and company credibility. Both of these factors are related to the emotional attachment of investors to the company and the role of the company's communication with investors Keywords: Corporate reputation, investment decision making, and beginner investors